Risk factors of hepatitis B virus infection among blood donors in Duhok city, Kurdistan Region, Iraq - Nawfal Hussein (Babol University of Medical Sciences, 2018)
Background: Hepatitis B virus (HBV) infection is a public health problem. The lack of information about the seroprevalence and risk factors is an obstacle for preventive public health plans to reduce the burden of viral hepatitis. Therefore, this study was conducted in Iraq, where no studies had been performed to determine the prevalence and risk factors of HBV infection. Methods: Blood samples were collected form 438 blood donors attending blood bank in Duhok city. Serum samples were tested for HBV core-antibodies (HBcAb) and HBV surface-antigen (HBsAg) by ELISA. Various risk factors were recorded and multivariate analysis was performed. Results: 5/438 (1.14%) of the subjects were HBsAg positive (HBsAg and HBcAb positive) and 36/438 (8.2%) were HBcAb positive. Hence, 41 cases were exposed to HBV and data analysis was based on that. Univariate analysis showed that there were significant associations between history of illegitimate sexual contact, history of alcohol or history of dental surgeries and HBV exposure (p<0.05 for all). Then, multivariate analysis was conducted to find HBV exposure predictive factors. It was found that history of dental surgery was a predictive factor for exposure to the virus (P=0.03, OR: 2.397). Conclusions: This study suggested that the history of dental surgery was predictive for HBV transmission in Duhok city. Further population-based study is needed to determine HBV risk factors in the society and public health plan based on that should be considered